Downregulation of the Proton-Activated Cl- Channel TMEM206 Inhibits Malignant Properties of Human Osteosarcoma Cells. (5th November 2021) - Peng, Fei; Li, Haohuan; Li, Jianping; Wang, Zhe
Abstract : Transmembrane protein 206 (TMEM206), a proton-activated chloride channel, has been implicated in various biochemical processes, including bone metabolism, and has emerged as a novel cancer-related protein in multiple tumor types. However, its role in primary malignant bone tumors, particularly in osteosarcoma (OS), remains unclear. This study is aimed at exploring the effects of TMEM206 gene silencing on the proliferation, migration, invasion, and metastasis of human OS cells in vitro and in vivo using an shRNA-knockdown strategy. We found that TMEM206 is frequently overexpressed and that high levels of TMEM206 correlated with clinical stage and pulmonary metastasis in patients with OS. We provided evidence that TMEM206-silenced OS cancer cells exhibit decreased proliferation, migration, and invasion in vitro . Mechanistically, we identified β -catenin, a key member of Wnt/ β -catenin signaling, as a downstream effector of TMEM206. TMEM206 silencing inhibits the Wnt/ β -catenin signaling pathway in expression rescue experiments, confirming that TMEM206 silencing attenuates OS cell tumorigenic behavior, at least in part, via the β -catenin mediated downregulation of Wnt/ β -catenin signaling. More importantly, TMEM206 knockdown-related phenotype changes were replicated in a xenograft nude mouse model where pulmonary metastases of OS cells were suppressed. Together, our results demonstrate that silencing TMEM206 negatively modulates the Wnt/ β -catenin signaling pathway via β -catenin to suppress proliferation, migration, invasion, and metastasis in OS carcinogenesis, suggesting TMEM206 as a potential oncogenic biomarker and a potential target for OS treatment.